Correlation of Sleep Duration, Emotional Eating, and Physical Activity with Students' Nutritional Status - Wahida Fitriyani; Atikah Adyas; Hidayatusy Syukrina Puteri (CV. CENDIKIA JENIUS INDONESIA, 2025)
Nutritional problems among university students have become a growing concern, as they may be influenced by unhealthy lifestyles such as insufficient sleep, emotional eating, and low physical activity. This study aimed to determine the correlation between sleep duration, emotional eating, and physical activity with the nutritional status of sixth-semester students of the Nursing Study Program at Mitra Indonesia University. This research employed a cross-sectional design with a quantitative approach. A total of 101 students were selected through purposive sampling. Data were collected from May to June 2025 using the Sleep Timing Questionnaire (STQ), Dutch Eating Behavior Questionnaire (DEBQ), International Physical Activity Questionnaire (IPAQ), and anthropometric measurements. Data were analyzed using univariate and bivariate methods with the Spearman Rank correlation test. The results showed that most respondents had adequate sleep duration (63.4%), high emotional eating scores (88.1%), and moderate physical activity (86.1%). However, there was no significant correlation between sleep duration (p=0.594), emotional eating (p=0.792), and physical activity (p=0.398) with nutritional status. Conclusion: There was no significant relationship between the three variables and students' nutritional status. Recommended to include additional variables such as academic stress, dietary patterns, and consumption of processed foods.